Social and Cultural of Stigma For Children With Stunting: A Literatur Review - Badrul Nurul Hisyam; Tantut Susanto (Babali Nursing Research)
Background: Children living with stunting face unique challenges influenced by social and cultural factors. Social stigmas arising from traditional cultures, norms, and beliefs exacerbate families' access to health services and negatively impact children's mental and emotional well-being. This literature review aims to identify factors related to social and cultural stigma affecting children with stunting within communities.